Alcance del término “esencia económica” en relación con el objeto social de una compañía - Villavicencio Ramírez, Patricia Stephanye (2019)
Ecuador is an importing and exporting country of commerce in the global way, which is why it must be followed by several rules for the attraction of foreign investment, in this case international agreements of double taxation so that taxpayers have tax benefits and double taxation is avoided. Agreements to Avoid Double Taxation, hereinafter CDI, are instruments that have been promoted as international organizations such as the OECD to avoid distortions in the application of tax burdens. Without the stipulations of the Agreements to Avoid Double Taxation, investors, companies and individuals, among others, we will not have the incentives to carry out business in other countries, for which the results of the fundamental importance for activities related to international relations, especially for foreign investment. The CDI, signed between Ecuador and Canada, considers as an adjustment criterion the place of residence or residence of the nationals of the countries; without prejudice of what is possible that they become avoidant practices of the taxpayers, being like this how they avoid or minimize the payment of the taxes, reason why based on the qualitative and quantitative data that the Internal Revenue service as main source to obtain Information, in addition to other sources such as INEC, Central Bank of Ecuador, among others, these data are public access. Therefore, based on cases such as business benefits and air and maritime transport, it can be observed whether or not there are avoidance practices in the CDI signed between Canada and Ecuador.